(untitled) (AYUSHDHARA, 2020)
Warts are benign epithelial hyperplasia manifesting mostly due to infection with human papilloma virus (HPV). The condition may affect the patient with or without pain, itching etc. Wart can became a stressful cosmetic problem. The references of Charmakeela in Kshudraroga adhikara in the Ayurvedic classics have a very close clinical proximity with warts. Kshara is one among the treatment choice for Charmakeela and used in Pratisaraneeya kshara form. Subcutaneous intralesional injection is one among the upgraded modalities of Pratisaraneeya ksharakarma. Kshara used as Ksharodhaka for this procedure. A 24 years old female patient with a common wart over the thumb visited the Salyatantra OPD, Govt. Ayurveda College Hospital Tripuithura in June 2019. The lesion was painless and without itching and was developed within a period of one month. The patient was undertaken for subcutaneous intralesional injection of Aragwadha ksharodhaka following proper lab investigations. The patient did not developed any adverse reactions or pain during the procedure. It was observed that, the wart shed off within a period of 7 days. There was no visible ulceration over the site of wart and healing happened leaving a minimum scar. Also there was visible healthy skin formation.